Implementasi Aplikasi Bank Sampah Berbasis Web Sri Ngesti Handayani Desa Karangsalam - Agus Subekti Panca Swantoro; Fahmi Fachri (Jurnal Media Informatika, 2025)
Waste is a serious problem that continues to increase along with population growth and changes in people's lifestyles. One solution to its management is the Waste Bank system, which allows people to save dry waste to gain economic and environmental benefits. This study aims to develop a software-based application to support the Waste Bank system, so that waste management and monitoring become more organized. The method used in developing this application is Rapid Application Development (RAD), which allows acceleration of the design and implementation process with high flexibility to changing needs. System testing was carried out using the black box testing method to assess the functionality of the application. The results of the study indicate that the developed application can assist in managing waste transactions well, providing convenience for users and managers of the Waste Bank. In conclusion, the application of the RAD methodology in developing this application can accelerate the implementation of waste management solutions, make the Waste Bank system more efficient, and provide benefits to the community in better waste management efforts.